Transformasi Literasi Kesehatan Reproduksi melalui Model Pemberdayaan Peer Educator Berbasis Participatory Action Research (PAR) Di SMK Kesehatan - Nadilla Pratiwi; Fikarwin Zuska; Frida Lina Tarigan; Donal Nababan; Henny Syahfitri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The low level of reproductive health literacy among adolescents and psychosocial barriers such as shame and taboos pose significant challenges to health education in school settings. This study aims to analyze the empowerment of female students as peer educators and its impact on reproductive health knowledge, attitudes, and skills using a Participatory Action Research (PAR) approach. The research utilizes an design within a PAR framework. Qualitative data were gathered through in-depth interviews with 6 key informants, while quantitative data were collected from 40 students in grades X and XI at SMK Kesehatan Dharma Analitika Medan via and questionnaires. Quantitative analysis employed the and the with a 95% significance level. The results indicate a significant improvement in knowledge and skills (p = 0.000) and positive attitude changes (p = 0.000) following the intervention. Student involvement throughout the PAR cycles effectively reduced communication barriers and increased a sense of ownership toward the program. In conclusion, the PAR-based peer educator approach is effective in enhancing reproductive health competencies and empowering adolescents as agents of change. Integrating this model into the PIK-R program is recommended to support the sustainability of health education in schools.